Becoming Teachers’ Little Epics: What digital storytelling might reveal - Radford, Linda; Aitken, Avril (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
This paper discusses pre-service teachers’ use of multi-modal tools to produce three-minute films in light of critical moments in their teaching practice. Two cases are considered; each centers on a film, a “little epic” that was produced by a future teacher who attempts to work within an anti-racist framework for social justice. Findings point to how multimodal tools are effective for engaging meaningfully with unresolved conflicts. However, in the face of trauma experienced, the future teachers’ efforts to work within a social justice framework may be pushed to the margins. This pedagogy / research sheds light on the workings of the inner landscape of becoming teachers, and highlights the dynamic of education as a psychic crisis compounded by the demands of the social.